The Diversity Of Macrozoobenthos River Aek Buru District Labuhan Batu Utara - Harahap, Arman (International Journal of Science, Technology & Management, 2023)
Benthos are organisms that live in the bottom of the waters, either animal or plant, living on the surface and in the bottom of the waters. This study aims to determine the diversity of Macrozoobenthos in the River Aek Buru. The study began in May 2021 to June 2021. Sampling of macrozoobenthos done using a Surber net. based on differences in the substrate at the base of the river. Macrozoobenthos found in the Aek Buru consists of two Phyla, namely the Arthropods and Mollusks. Phylum Arthropoda are found is of the class of Insects belonging to the genus Hydropsyche, Polycentropus, psephenus, Dryops, Anthopotamu, Acroneuria and Triops. The phylum of Mollusks that are found are from a class of Bilvavia included in the Genus Corbicula and of the class of Gastropods of the Genera Melanoides and Melanatria. The abundance of macrozoobenthos of the highest on each of the stations is Polycentropus (66,67 ind/L) and Potadoma (266,67 ind/L). The abundance of macrozoobenthos of the highest found is Melanatria by 622,2 ind/L. Based on the value of the Index of Diversity (H) (0,367 – 0,602) the index of dominance (C) (0,132 – 0,386) and the evenness (E) (0,367 – 0,602) River Aek Buru in the category good condition with high species diversity. Physical and chemical factors of the water body capable of supporting life macrozoobenthos.